Comparison of Titer and Signal to Noise (S/N) for Determination of Anti-drug Antibody Magnitude Using Clinical Data from an Industry Consortium - Marta Starcevic Manning; Mohamed Hassanein; Michael A. Partridge; Vibha Jawa; Johanna Mora; Josiah Ryman; Breann Barker; Christian Braithwaite; Kevin Carleton; Laura Hay; Charles Hottenstein; Robert J. Kubiak; et al. (The AAPS Journal, 2022)
During biotherapeutic drug development, immunogenicity is evaluated by measuring anti-drug antibodies (ADAs). The presence and magnitude of ADA responses is assessed using a multi-tier workflow where samples are screened, confirmed, and titered. Recent reports suggest that the assay signal to noise ratio ( S / N ) obtained during the screening tier correlates well with titer. To determine whether S / N could more broadly replace titer, anonymized ADA data from a consortium of sponsors was collected and analyzed. Datasets from clinical programs with therapeutics of varying immunogenicity risk levels (low to high), common ADA assay platforms (ELISA and MSD) and formats (bridging, direct, solid-phase extraction with acid dissociation), and titration approaches (endpoint and interpolated) were included in the analysis. A statistically significant correlation between S / N and titer was observed in all datasets, with a strong correlation (Spearman’s r > 0.8) in 11 out of 15 assays (73%). For assays with available data, conclusions regarding ADA impact on pharmacokinetics and pharmacodynamics were similar using S / N or titer. Subject ADA kinetic profiles were also comparable using the two measurements. Determination of antibody boosting in patients with pre-existing responses could be accomplished using similar approaches for titer and S / N . Investigation of factors that impacted the accuracy of ADA magnitude measurements revealed advantages and disadvantages to both approaches. In general, S / N had superior precision and ability to detect potentially low affinity/avidity responses compared to titer. This analysis indicates that S / N could serve as an equivalent and in some cases preferable alternative to titer for assessing ADA magnitude and evaluation of impact on clinical responses. Graphical Abstract

Investigating interactions between phentermine, dexfenfluramine, and 5-HT2C agonists, on food intake in the rat - Andrew J. Grottick; Kevin Whelan; Erin K. Sanabria; Dominic P. Behan; Michael Morgan; Carleton Sage (Psychopharmacology, 2015)